The influence of the twin peg design on femoral Interface temperature and maximum load to failure in cemented Oxford unicompartmental knee arthroplasty. (June 2018) - Reiner, Tobias; Schwarze, Martin; Panzram, Benjamin; Klotz, Matthias C.; Bitsch, Rudi G.; Jaeger, Sebastian
Abstract: Background: The twin peg femoral component was introduced for the cemented Oxford unicondylar knee to increase implant stability. The aim of this experimental study was to investigate the influence of the twin peg design on femoral interface temperature and maximum load to failure in comparison to the single peg design. Methods: In this experimental study medial Oxford unicompartmental knee arthroplasty was performed in 12 pairs of fresh-frozen human knees. A cemented femoral single peg component was implanted on the one side (group A) and a cemented twin peg component on the other side (group B). Cement interface temperature was continuously monitored during the procedure. Maximum tensile forces of the femoral components were measured by pull-out tests. Findings: Maximum femoral interface temperatures did not reach critical values for heat necrosis of the bone in group A (mean 28.4, SD 1.2 °C) or group B (mean 27.6, SD 0.5 °C). The maximum load to failure was significantly higher in the twin peg group (mean 3628.41, SD 650.92 N) compared to the single peg group (mean 2979, SD 781 N) ( P  = 0.016). Interpretation: Our experiments showed higher load to failure for the twin peg design compared to the single peg design without raising the risk of heat necrosis at the interfacial bone. The twin peg component offers a save alternative to the single peg component in a cadaveric setting. Highlights: Interface temperatures did not reach critical values in both groups. Maximum load to failure was significantly higher in the twin peg group. Both implant designs offer secure fixation in an experimental setting.